COMMON PRE-ANALYTICAL ERRORS IN BLOOD SAMPLE COLLECTION - Dina Fauziah; Anditri Weningtyas (STIKes Kepanjen, 2022)
The demand for accurate laboratory examinations is increasing. However, other than laboratory personnel, there is still a high number of medical staff that are unaware of it. Even though they play a very important role in the pre-analytic aspect of laboratory examination, that is blood drawing. In this review, we elaborately explain common mishaps in blood drawing practice and some components that need more attention when collecting blood for laboratory examination.